MODIFIKASI BAHAN BAKU PERMEN KALAMANSI DENGAN PENAMBAHAN BUAH NAGA MERAH [Modification of Calamansi Candy Raw Material with Addition of Red Dragon Fruit] - Kurnia Harlina Dewi; Valentina Bernita; Sigit Mujiharjo (Jurnal Teknologi & Industri Hasil Pertanian, 2019)
The red dragon fruit is a highly nutritious fruit that can enrich the weakness of the nutritional value of calamansi candy. The purpose of this study was to know the effect of the red dragon fruit with and without seeds to the properties of calamansi candy, as well as to determine the best percentage of dragon fruit addition for consumers preferred calamansi candy. This research was conducted at the Laboratory of Agricultural Tech-nology and FMIPA at the Bengkulu University. Data were analyzed descritiply and pre-sented in graphical form. The results showed that the greater the concentration of the red dragon fruit in the process of calamansi candy, the higher the moisture content, ash con-tent, pH, vitamin C, and total acid. However, the greater addition of red dragon fruit without seeds, the vitamin C content decreased. The most preferred calamansi candy by consumers was those either with or without seeds of 10% red dragon fruit addi-tion. The composition of this candy was met SNI criteria with carbohydrate 7.41% and 6.59%, protein 1.79% and 1,45%, and reducing sugar 49% and 30.5% for calamansi can-dy without and with seed of red dragon, respectively.